Profitabilitas sebagai Pemoderasi Nilai Saham Perusahaan Industri Barang Konsumsi - Sari, Widya; Hartono, Hartono; Audrey, Fiona (E-Jurnal Akuntansi; Vol 30 No 3 (2020), 2020)
This study aims to determine and analyze how the influence of Current Ratio, Inventory Turnover, Fixed Asset Turnover and Debt to Equity Ratio on Stock Price and Profitability as a moderating variable to consumer goods sector companies listed on the Indonesia Stock Exchange (IDX). Population in this study are 39 companies and 14 companies used as samples. This research uses purposive sampling method. The results of this study indicate that the Fixed Asset Ratio and Debt to Equity Ratio affects stock value. By using profitability as a moderator, Current Ratio and Debt to Equity Ratio affects the value of the stock. Keywords: Current Ratio (CR); Inventory Turnover (ITO);  Fixed Asset Turnover (FAT); Debt to Equity Ratio (DER) ; Stock Price.